Influenza A (H1N1): Past season’s wonder flu in Vojvodina - Joveš-Sević Biljana; Obradović Dušanka; Batranović Uroš; Stojanović Miloš; Sovilj-Gmizić Stanislava; Bošković Tatjana (Vojnosanitetski Pregled)
Background/Aim. Influenza A (H1N1) re-emerged in the human population during 2009. The aim of this study was to describe characteristics, laboratory findings, clinical presentation and treatment outcome among patients with influenza A (H1N1) infection. Methods. The study was performed at the Institute for Pulmonary Diseases of Vojvodina including all the patients hospitalized at the Intensive Care Unit or High Dependency Unit with confirmed, probable or suspected Influenza A (H1N1) infection between November 6th, 2009 and April 13th, 2010. Results. Among 64 patients Influenza A (H1N1) infection was confirmed by rt-PCR in 50, defined as probable in 7 and as suspected in 6 patients. There was an equal number of male and female patients. Their mean age was 46 years (SD ± 12.1). None of the patients were vaccinated against influenza. Comorbidities were present in 37 (58%) patients. There were 29 (45%) obese patients. Three patients were pregnant. The median time from symptom onset to hospital admission was 5 days (IQR 4-7). At admission, the median Modified Early Warning Score (MEWS) was 4 (IQR 3-6). The most common presenting symptoms were cough (100%) and fever (89%). The mean oxygen saturation at admission was 85.3% (SD 9.0). Auscultatory finding of wheesing in the absence of a chronic lung disease was found in 10 (15.6%) patients. Leukopenia was noted in 23 (35.9%) patients, and thrombocytopenia in 14 (21.9%) patients. Aspartate aminotransferase values were elevated in 41 (64.1%) patients, alanine aminotransferase in 32 (50%) patients, and creatine kinase in 36 (56.2%) patients. Opacities on an initial chest radiograph were predominantly patchy and the median number of the lung fields involved was 1 (IQR = 0-3). The non-survivors had statistically significantly higher MEWS at admission (p = 0.0001), lower oxygen saturation (p = 0.001), more lung fields involved on an initial chest radiograph (p = 0.006), wheezing in the absence of chronic lung disease (p = 0.02) and elevated aspartat aminotransferase (p = 0.02) and creatine kinase (p = 0.03). Acute respiratory disstress developed in 21 (32.9%) patients, and mechanical ventilation was required in 23 (36.1%) patients. Septic shock developed in 12 (18.7%) patients, and 19 (29.7%) patients had a multi-organ dysfunction. The overall hospital mortality was high - 20.3% (95% CI, 11.3%-32.2%; n = 13), and especially so among the patients who required mechanical ventilation - 56.5% (95% CI, 36.8%-74.4%). Conclusion. Timely initiation of antiviral therapy and early recognition of critically ill are important factors for reducing mortality.